An Analysis of Politeness Strategies Used in Frozen 2 Movie Based on Brown and Levinson's Theory - Kustianingsih Kustianingsih; Hastri Firharmawan (SIMPLE: International Journal of English Education, 2025)
This study investigates the use of politeness strategies in the animated film Frozen 2 using Brown and Levinson’s theory of politeness. As a continuation of Disney's popular franchise, Frozen 2 features a variety of characters interacting in emotionally charged and socially complex situations. This research aims to identify and analyze the types of politeness strategies employed by the main characters and to understand the purposes behind their usage. The qualitative method was applied in this study by collecting data from the script of the movie and analyzing utterances that reflect politeness strategies. The findings reveal the total number and types of politeness strategies used in the film, including bald on record, positive politeness, negative politeness, and off record strategies. The most frequently used strategy was positive politeness, which indicates the characters' tendency to build solidarity and maintain friendly relationships. The study concludes that Frozen 2 demonstrates a wide range of politeness strategies, reflecting the characters' social dynamics, personal intentions, and emotional development. This research contributes to understanding how language and politeness intertwine in media targeted at young audiences and may serve as a reference for further linguistic and discourse analysis.